A Case of Primary Intraventricular Brain Abscess in a Child: A Challenge to Conquer - Bajracharya, Shristi; Shrestha, Prabin; Singh, Anish M; Shrestha, Reshma; Shakva, Shanta C (Nepal Journal of Neuroscience, 2016)
Primary intraventricular brain abscess is a rare entity. Not many cases are reported yet. Moreover, proper guidelines for the treatment, conservative treatment or surgery, has not yet been established. Its outcome is also unpredictable and usually poor. We present a 11-year-old girl with wide spread intraventricular brain abscess. There was no obvious cause for the abscess formation. Cardiac status was normal by history and ECHO. She was treated surgically with external ventricular drainage (EVD). There was significant improvement after EVD. Intraventricular flushing was done with the solution of injection Gentamycin and hydrocortisone. However, the patient expired while planned for discharge from the hospital due to sudden cardiac arrest. A bigger study is needed to assess the various factors of intraventricular brain abscess including epidemiology, treatment, outcome etc in the Nepalese context. Nepal Journal of Neuroscience 12:88-90, 2015